Combining an FMCW radar system with FSK modulation to a joint communication and sensing system - Faghih-Naini, Samira; Schneider, Michael; Peters, Sebastian; Weigel, Robert; Reißland, Torsten (International Journal of Microwave and Wireless Technologies, 2025)
Due to the rising occupancy of the radio spectrum, new strategies for covering the ever increasing amount of data are necessary. This work presents a system for integrating data transmission into a frequency-modulated continuous wave (FMCW) radar by modulating the radar signal with frequency shift keying (FSK). The system offers a high chirp bandwidth of 5 GHz and uses the 60 GHz band. The FSK carrier frequency affects the noise level. A higher frequency leads to a lower noise floor due to 1/f-noise but requires a higher sampling rate. Therefore, 15 MHz was chosen as a compromise. A high data rate allows for a fast data transmission but requires a short chirp time, which leads to a noisier frequency chirp. The radar parameters are also affected by this choice. This leads to a baud rate of 20.8 kbit/s. With a higher order FSK, higher data rates are possible. This proves that the data transmission via FMCW radar signals is possible and a first choice if lower data rates are sufficient, because the hardware effort is comparatively low.
CRIS-Team Scopus Importer:2025-05-16
Keywords: digital signal processing; frequency shift keying; millimeter wave communication; millimeter wave radar